Paneer whey-apricot drink: Effect of pectinase treatment, dilution ratio, and yeast co-culture - Jindal, Harsh; Panjagari, Narender Raju; Ganguly, Sangita; Vij, Shilpa (Indian Journal of Dairy Science, 2025)
This study aimed to optimize the concentration of pectinase enzyme to enhance juice extraction from apricot pulp. It also determined the optimal level of paneer whey as a water substitute in must preparation and standardized the percentage of yeast co-culture to produce high-quality paneer whey-apricot wine. Apricots from Ladakh were pulped to preserve them. The paneer whey was defatted and deproteinized to prevent any adverse effects on the finished product’s quality. Due to the high fiber content of apricots, pectinase enzyme was used to break down the pectin in the pulp and release more juice and soluble components. Pectinase was tested at different concentrations (0.2%, 0.5%, and 1%), with 0.5% proving to be optimal because it significantly increased juice yield. To prepare must, this juice was diluted with treated whey in different ratios (1:1 to 3:1). Various chemical parameters were analyzed, including ethanol, methanol, antioxidants, sugar profiles, and sensory evaluation of the different dilutions to assess the acceptability of the final product. The 2:1 dilution received better acceptance compared to the 1:1 and 3:1 dilutions. The 1:1 dilution wine had a thick, intense fruity flavor with high acidity, while the 3:1 dilution resulted in a very light flavor and color, making it less acceptable. Considering the higher ethanol production and sensory ratings, the 2:1 dilution ratio was determined to be the optimal choice for producing good-quality paneer whey-apricot wine. The study also analyzed the effect of varying yeast co-culture concentrations on the final wine. Based on the ethanol content in the final wine, 7.5% yeast co-culture was optimized. Finally, the optimized conditions of pectinase, dilution, and yeast co-culture percentages were used to prepare the final product.